ANALISIS PENGENDALIAN PIUTANG UNTUK MEMINIMALKAN RESIKO PIUTANG TAK TERTAGIH PADA PT SAMUDERA MANDIRI SENTOSA - Aimbu, Gitania; Karamoy, Herman; Tangkuman, Steven J. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Receivables are one of the current assets owned by a company as a result of a credit sale made by the company. However, the existence of receivables owned by a company will cause a risk of bad debts. At PT Samudera Mandiri Sentosa itself also has uncollectible accounts due to the ineffective control of accounts receivable carrid out by the management department. The purpose of this research is to know how to control accounts receivable to minimize the risk of bad debts at PT Samudera Mandiri Sentosa. This research use descriptive qualitative research in which the authors analyze accounts receivable data and provide a detailed description of the research results. The data source of this writing comes from interviewes and observations conducted at PT Samudera Mandiri Sentosa. Based on the analysis of accounts receivable from the last three years (2018-2020) the percentage of uncollectible accounts has increased due to human errors and system errors that have occured within the company, therefore it is necessary to improve the receivables control strategy. The results of the research obtained after implementing in control strateges, namely uncollectible accounts have decreased.